Per- and polyfluoroalkyl substances (PFAS) and miscarriage: The Norwegian Mother, Father and Child Cohort study - Thea Grindstad; Maria C. Magnus; Alessandro Di Nallo; Cecilia Høst Ramlau-Hansen; Zeyan Liew; Hans Ivar Hanevik; Line S. Haug; Gro D. Andersen; Tormod Rogne; Eleni Papadopoulou; Per Magnus; Siri E. Håberg; et al. (Environmental Research, 2026)

Response of a semi-enclosed sea to perturbed freshwater and open ocean salinity forcing - Lars Arneborg; Magnus Hieronymus; Per Pemberton; Ye Liu; Sam T. Fredriksson (Ocean Science, 2026)
The sensitivity of Baltic Sea salinities to changed freshwater forcing and other forcing factors have been debated during the last decades, since changed salinities would have large impacts on the marine ecosystems, and since this parameter still shows a high degree of uncertainty in regional climate projections. In this study, we performed a sensitivity experiment where freshwater forcing and salinities at the outer boundaries of the North Sea were perturbed in a systematic way in order to obtain a second-order Taylor polynomial of the statistical steady state mean salinity. The polynomial was constructed based on perturbations of a 57 year long hindcast run for the period 1961–2017 with a regional ocean model covering the North Sea and the Baltic Sea. The results show that the Baltic Sea is highly sensitive to freshwater forcing, and that about one third of the boundary salinity change propagates into the Baltic Sea. The results are also analysed in terms of a total exchange flow analysis in the entrance region, and it is found that the Baltic Sea salinity sensitivity to freshwater forcing to a large degree can be explained by increased freshwater input causing (1) dilution inside the Baltic Sea, (2) decreased inflows caused by changes to the mean sea level gradient in the entrance region, and (3) reduced inflow salinities due to recirculation of outflowing Baltic Sea water in the entrance region where the inflow water consists of about two parts outflowing Baltic water and one part North Sea water. Besides providing new understanding of the processes that govern the Baltic Sea salinity sensitivity to freshwater forcing, the results of this study provide means of quickly assessing Baltic Sea salinity changes based on changes of North-East Atlantic salinities and Baltic Sea freshwater forcing.

Can wetlands designed for flood attenuation efficiently remove nitrogen from agricultural runoff? - Josefin E. Nilsson; Joachim Audet; Per Magnus Ehde; Stefan E.B. Weisner; Antonia Liess (Journal of Environmental Management, 2025)

Effects of stand structural attributes on oak recruitment in mixed temperate forests - Nora S. Pohl; Per-Ola Hedwall; Jorge Aldea; Annika M. Felton; Emile S. Gardiner; Luca Muraro; Björn Nordén; Magnus Löf (Forest Ecology and Management, 2025)

Forest fertilization transiently increases soil CO2 efflux in young Norway spruce stands in Sweden - Charlotta Håkansson; Per-Ola Hedwall; Martin Karl-Friedrich Bader; Monika Strömgren; Magnus Axelsson; Johan Bergh (Agricultural and Forest Meteorology, 2025)

Increase of chemical weathering in the Lena River Catchment under a warmer climate - Xiaole Sun; Carl-Magnus Mörth; Don Porcelli; Christoph Humborg; Liselott Kutscher; Catherine Hirst; Melissa J. Murphy; Trofim Maximov; Roman E. Petrov; Per S. Andersson (Chemical Geology, 2024)

Enhancing nitrogen removal through macrophyte harvest and installation of woodchips-based floating beds in surface-flow constructed wetlands - Maidul I. Choudhury; Josefin E. Nilsson; Samuel Hylander; Marc Hauber; Per Magnus Ehde; Stefan E.B. Weisner; Antonia Liess (Chemosphere, 2024)

Iron isotopes reveal seasonal variations in the mechanisms for iron-bearing particle and colloid formation in the Lena River catchment, NE Siberia - Catherine Hirst; Per S. Andersson; Carl-Magnus Mörth; Melissa J. Murphy; Melanie Schmitt; Ellen Kooijman; Liselott Kutscher; Roman Petrov; Trofim Maximov; Don Porcelli (Geochimica et Cosmochimica Acta, 2023)

Contrasting distribution and speciation of sedimentary organic phosphorus among different basins of the Baltic Sea - Emil Rydin; Elias Broman; Kasper Reitzel; Kaarina Lukkari; Martijn Hermans; Linda Kumblad; Magnus Karlsson; Anna Apler; Bo Ek; Per J. R. Sjöberg (Limnology and Oceanography, 2023)
Recycling of phosphorus (P) from deoxygenated sediments perpetuates eutrophic conditions in parts of the Baltic Sea. Sedimentary organic P is a major source of dissolved P to the water column, but also a sink for permanent P burial. The mechanisms behind these two pathways are, however, largely unknown. Using new methods, we determined P in DNA and phospholipids, which are both found in all organisms. We also identified inositol phosphates that are particularly important in eukaryotes. Sediment cores were collected from contrasting basins in the Baltic Sea to study their relative contribution to the total P pool. We found high DNA‐P/phospholipid‐P ratios in surface sediments from the Bothnian Bay and Bothnian Sea. However, these ratios were low throughout profiles in euxinic Baltic Proper sediments. The elevated ratios present in sediments overlain by oxic bottom waters might indicate the presence of a microbial community stimulated by bioturbation, whereas the low DNA‐P/phospholipid‐P ratios in Baltic Proper sediments likely indicate an energy‐limited microbial community, typical to the “deep biosphere” environment. Inositol‐P was almost absent in euxinic Baltic Proper sediments that had a low total P amount compared to those in the other basins. We suggest that variability in the composition of sedimentary microbial communities among the Baltic Sea basins might cause differences in organic P forms that in turn affects its turnover.

Elucidating the fine-scale structural morphology of nanocellulose by nano infrared spectroscopy - Nikolay Kotov; Per A. Larsson; Karishma Jain; Tiffany Abitbol; Adrian Cernescu; Lars Wågberg; C. Magnus Johnson (Carbohydrate Polymers, 2023)

The serotonin receptor 3E variant is a risk factor for female IBS-D - Nikola Fritz; Sabrina Berens; Yuanjun Dong; Cristina Martínez; Stefanie Schmitteckert; Lesley A. Houghton; Miriam Goebel-Stengel; Verena Wahl; Maria Kabisch; Dorothea Götze; Mauro D’Amato; Tenghao Zheng; et al. (Journal of Molecular Medicine, 2022)
Irritable bowel syndrome (IBS) is a gut-brain disorder of multifactorial origin. Evidence of disturbed serotonergic function in IBS accumulated for the 5-HT 3 receptor family. 5-HT 3 Rs are encoded by HTR3 genes and control GI function, and peristalsis and secretion, in particular. Moreover, 5-HT 3 R antagonists are beneficial in the treatment of diarrhea predominant IBS (IBS-D). We previously reported on functionally relevant SNPs in HTR3A c.-42C > T (rs1062613), HTR3C p.N163K (rs6766410), and HTR3E c.*76G > A (rs56109847 = rs62625044) being associated with IBS-D, and the HTR3B variant p.Y129S (rs1176744) was also described within the context of IBS. We performed a multi-center study to validate previous results and provide further evidence for the relevance of HTR3 genes in IBS pathogenesis. Therefore, genotype data of 2682 IBS patients and 9650 controls from 14 cohorts (Chile, Germany (2), Greece, Ireland, Spain, Sweden (2), the UK (3), and the USA (3)) were taken into account. Subsequent meta-analysis confirmed HTR3E c.*76G > A (rs56109847 = rs62625044) to be associated with female IBS-D (OR = 1.58; 95% CI (1.18, 2.12)). Complementary expression studies of four GI regions (jejunum, ileum, colon, sigmoid colon) of 66 IBS patients and 42 controls revealed only HTR3E to be robustly expressed. On top, HTR3E transcript levels were significantly reduced in the sigma of IBS patients ( p = 0.0187); more specifically, in those diagnosed with IBS-D ( p = 0.0145). In conclusion, meta-analysis confirmed rs56109847 = rs62625044 as a risk factor for female IBS-D. Expression analysis revealed reduced HTR3E levels in the sigmoid colon of IBS-D patients, which underlines the relevance of HTR3E in the pathogenesis of IBS-D.

Multiple drivers of large‐scale lichen decline in boreal forest canopies - Per‐Anders Esseen; Magnus Ekström; Anton Grafström; Bengt Gunnar Jonsson; Kristin Palmqvist; Bertil Westerlund; Göran Ståhl (Global Change Biology, 2022)
Thin, hair‐like lichens ( Alectoria , Bryoria , Usnea ) form conspicuous epiphyte communities across the boreal biome. These poikilohydric organisms provide important ecosystem functions and are useful indicators of global change. We analyse how environmental drivers influence changes in occurrence and length of these lichens on Norway spruce ( Picea abies ) over 10 years in managed forests in Sweden using data from >6000 trees. Alectoria and Usnea showed strong declines in southern‐central regions, whereas Bryoria declined in northern regions. Overall, relative loss rates across the country ranged from 1.7% per year in Alectoria to 0.5% in Bryoria . These losses contrasted with increased length of Bryoria and Usnea in some regions. Occurrence trajectories (extinction, colonization, presence, absence) on remeasured trees correlated best with temperature, rain, nitrogen deposition, and stand age in multinomial logistic regression models. Our analysis strongly suggests that industrial forestry, in combination with nitrogen, is the main driver of lichen declines. Logging of forests with long continuity of tree cover, short rotation cycles, substrate limitation and low light in dense forests are harmful for lichens. Nitrogen deposition has decreased but is apparently still sufficiently high to prevent recovery. Warming correlated with occurrence trajectories of Alectoria and Bryoria , likely by altering hydration regimes and increasing respiration during autumn/winter. The large‐scale lichen decline on an important host has cascading effects on biodiversity and function of boreal forest canopies. Forest management must apply a broad spectrum of methods, including uneven‐aged continuous cover forestry and retention of large patches, to secure the ecosystem functions of these important canopy components under future climates. Our findings highlight interactions among drivers of lichen decline (forestry, nitrogen, climate), functional traits (dispersal, lichen colour, sensitivity to nitrogen, water storage), and population processes (extinction/colonization).

Reserves, resilience and dynamic landscapes 20 years later - Jan Bengtsson; Per Angelstam; Thomas Elmqvist; Urban Emanuelsson; Carl Folke; Margareta Ihse; Fredrik Moberg; Magnus Nyström (Ambio, 2021)

Contagiousness in treated HIV-1 infection - Jaran Eriksen; Jan Albert; Maria Axelsson; Torsten Berglund; Johanna Brännström; Hans Gaines; Magnus Gisslén; Peter Gröön; Per Hagstam; Lars Navér; Karin Pettersson; Jenny Stenkvist; et al. (Infectious Diseases, 2021)

Quantifying errors in GNSS antenna calibrations - Sten Bergstrand; Per Jarlemark; Magnus Herbertsson (Journal of Geodesy, 2020)
We evaluated the performance of GNSS absolute antenna calibrations and its impact on accurate positioning with a new assessment method that combines inter-antenna differentials and laser tracker measurements. We thus separated the calibration method contributions from those attainable by various geometric constraints and produced corrections for the calibrations. We investigated antennas calibrated by two IGS-approved institutions and in the worst case found the calibration’s contribution to the vertical component being in excess of 1 cm on the ionosphere-free frequency combination L3. In relation to nearby objects, we gauge the $$1σ $$ 1 σ accuracies of our method to determine the antenna phase centers within $$± \,0.38$$ ± 0.38 mm on L1 and within $$± \,0.62$$ ± 0.62 mm on L3, the latter applicable to global frame determinations where atmospheric influence cannot be neglected. In addition to antenna calibration corrections, the results can be used with an equivalent tracker combination to determine the phase centers of as-installed individual receiver antennas at system critical sites to the same level without compromising the permanent installations.

Lack of evidence of vertical transmission of piscine myocarditis virus in Atlantic salmon ( Salmo salar L.) - Aase B. Mikalsen; Morten Lund; Farah Manji; Mari Viken Kjønstad; Per Helge Bergtun; Gordon Ritchie; Vidar Aspehaug; Magnus Devold; Øystein Evensen (Journal of Fish Diseases, 2020)

Amyloid formation of bovine insulin is retarded in moderately acidic pH and by addition of short-chain alcohols - David Bernson; Almedina Mecinovic; Md Tuhin Abed; Fredrik Limé; Per Jageland; Magnus Palmlöf; Elin K. Esbjörner (European Biophysics Journal, 2020)
Protein aggregation and amyloid formation are associated with multiple human diseases, but are also a problem in protein production. Understanding how aggregation can be modulated is therefore of importance in both medical and industrial contexts. We have used bovine insulin as a model protein to explore how amyloid formation is affected by buffer pH and by the addition of short-chain alcohols. We find that bovine insulin forms amyloid fibrils, albeit with different rates and resulting fibril morphologies, across a wide pH range (2–7). At pH 4.0, bovine insulin displayed relatively low aggregation propensity in combination with high solubility; this condition was therefore chosen as basis for further exploration of how bovine insulin’s native state can be stabilized in the presence of short-chain alcohols that are relevant because of their common use as eluents in industrial-scale chromatography purification. We found that ethanol and isopropanol are efficient modulators of bovine insulin aggregation, providing a three to four times retardation of the aggregation kinetics at 30–35% (vol/vol) concentration; we attribute this to the formation of oligomers, which we detected by AFM. We discuss this effect in terms of reduced solvent polarity and show, by circular dichroism recordings, that a concomitant change in α-helical packing of the insulin monomer occurs in ethanol. Our results extend current knowledge of how insulin aggregates, and may, although bovine insulin serves as a simplistic model, provide insights into how buffers and additives can be fine-tuned in industrial production of proteins in general and pharmaceutical insulin in particular.

On the role of sedimentological processes controlling phosphorus burial in the coastal zone of the Baltic Sea - Olof Magnus Karlsson; Andreas Christoffer Bryhn; Lars Håkanson; Joakim Hållén; Per Jonsson; Jan Mikael Malmaeus; Emil Rydin (Limnology and Oceanography, 2019)

A simple approach for restoration of differentiation and function in cryopreserved human hepatocytes - Magnus Ölander; Jacek R. Wiśniewski; Inken Flörkemeier; Niklas Handin; Jozef Urdzik; Per Artursson (Archives of Toxicology, 2019)

Novel Features and Abnormal Pattern of Cerebral Glucose Metabolism in Spinocerebellar Ataxia 19 - Martin Paucar; Åsa Bergendal; Peter Gustavsson; Magnus Nordenskjöld; José Laffita-Mesa; Irina Savitcheva; Per Svenningsson (The Cerebellum, 2018)

Comprehensive phylogeny of the laughingthrushes and allies (Aves, Leiothrichidae) and a proposal for a revised taxonomy - Alice Cibois; Magnus Gelang; Per Alström; Eric Pasquet; Jon Fjeldså; Per G. P. Ericson; Urban Olsson (Zoologica Scripta, 2018)
DNA phylogenies have gradually shed light on the phylogenetic relationships of the large babbler group. We focus in this study on the family Leiothrichidae (laughingthrushes and “song babblers”), which represents the largest clade of babblers in terms of species diversity. Our phylogeny includes all genera and 82% of the recognized species, using mitochondrial and nuclear loci. The sister group to Leiothrichidae is composed of the Pellorneidae (“jungle babblers”) plus the genus Alcippe . Within Leiothrichidae, four strongly supported primary clades (A–D) are recovered. Clade A includes Grammatoptila , Laniellus and Cutia . Clade B includes a large group of laughingthrushes, all of them classified in Trochalopteron . In Clade C, the two laughingthrushes endemic to southern India, T. fairbanki and T. cachinnans , which have recently been proposed to be placed in the newly erected genus Montecincla , form a sister clade to the group comprising the “song babblers” ( Lioptila , Leiothrix , Heterophasia , Minla , Liocichla , Actinodura , Chrysominla , Siva , and Sibia ). Clade D includes the African babblers ( Turdoides , Phyllanthus , Kupeornis ), Asian relatives ( Argya , Acanthoptila , Chatarrhaea ) and all remaining laughingthrushes ( Garrulax ). The time estimates suggest that the early diversification of the Leiothrichidae occurred in the mid‐Miocene, a period that corresponds to the diversification of many passerine groups in Asia. A revised taxonomic classification of the family is proposed in the light of these results.

Impact on affected families and society of severe rotavirus infections in Swedish children assessed in a prospective cohort study - Anh Nhi Tran; Magnus Husberg; Rutger Bennet; Maria Brytting; Per Carlsson; Margareta Eriksson; Jann Storsaeter; Barbro Österlin; Kari Johansen (Infectious Diseases, 2018)

Increased mast cell degranulation and co-localization of mast cells with the NMDA receptor-1 during healing after Achilles tendon rupture - Md. Abdul Alim; Paul W. Ackermann; Pernilla Eliasson; Parmis Blomgran; Per Kristiansson; Gunnar Pejler; Magnus Peterson (Cell and Tissue Research, 2017)

Chemical changes in organic matter after fungal colonization in a nitrogen fertilized and unfertilized Norway spruce forest - César Nicolás; Juan P. Almeida; Magnus Ellström; Adam Bahr; Sharon E. Bone; Nicholas P. Rosenstock; John R. Bargar; Anders Tunlid; Per Persson; Håkan Wallander (Plant and Soil, 2017)

Gravity Compensation Method for Combined Accelerometer and Gyro Sensors Used in Cardiac Motion Measurements - Magnus Reinsfelt Krogh; Giang M. Nghiem; Per Steinar Halvorsen; Ole Jakob Elle; Ole-Johannes Grymyr; Lars Hoff; Espen W. Remme (Annals of Biomedical Engineering, 2017)

Six-week follow-up after HIV-1 exposure: a position statement from the Public Health Agency of Sweden and the Swedish Reference Group for Antiviral Therapy - Hans Gaines; Jan Albert; Maria Axelsson; Torsten Berglund; Magnus Gisslén; Anders Sönnerborg; Anders Blaxhult; Gordana Bogdanovic; Maria Brytting; Christina Carlander; Leo Flamholc; Per Follin; et al. (Infectious Diseases, 2016)

Identifying Hot Spots of Agricultural Nitrogen Loss Within the Baltic Sea Drainage Basin - Hans Estrup Andersen; Gitte Blicher-Mathiesen; Hans Thodsen; Peter Mejlhede Andersen; Søren E. Larsen; Per Stålnacke; Christoph Humborg; Carl-Magnus Mörth; Erik Smedberg (Water, Air, & Soil Pollution, 2016)

Population collapses in introduced non-indigenous crayfish - Alfred Sandström; Magnus Andersson; Anders Asp; Patrik Bohman; Lennart Edsman; Fredrik Engdahl; Per Nyström; Marika Stenberg; Pia Hertonsson; Trude Vrålstad; Wilhelm Granèli (Biological Invasions, 2014)

Genetic variants in loci 1p13 and 9p21 and fatal coronary heart disease in a Norwegian case-cohort study - Mona Dverdal Jansen; Gun Peggy Knudsen; Ronny Myhre; Gudrun Høiseth; Jørg Mørland; Øyvind Næss; Kristian Tambs; Per Magnus (Molecular Biology Reports, 2014)

Carbon Dioxide-Mediated Generation of Hybrid Nanoparticles for Improved Bioavailability of Protein Kinase Inhibitors - Gérald Jesson; Magnus Brisander; Per Andersson; Mustafa Demirbüker; Helene Derand; Hans Lennernäs; Martin Malmsten (Pharmaceutical Research, 2014)
Purpose A versatile methodology is demonstrated for improving dissolution kinetics, gastrointestinal (GI) absorption, and bioavailability of protein kinase inhibitors (PKIs). Methods The approach is based on nanoparticle precipitation by sub- or supercritical CO 2 together with a matrix-forming polymer, incorporating surfactants either during or after nanoparticle formation. Notably, striking synergistic effects between hybrid PKI/polymer nanoparticles and surfactant added after particle formation is investigated. Results The hybrid nanoparticles, consisting of amorphous PKI embedded in a polymer matrix (also after 12 months), display dramatically increased release rate of nilotinib in both simulated gastric fluid and simulated intestinal fluid, particularly when surfactants are present on the hybrid nanoparticle surface. Similar results indicated flexibility of the approach regarding polymer identity, drug load, and choice of surfactant. The translation of the increased dissolution rate found in vitro into improved GI absorption and bioavalilability in vivo was demonstrated for male beagle dogs, where a 730% increase in the AUC 0–24h was observed compared to the benchmark formulation. Finally, the generality of the formulation approach taken was demonstrated for a range of PKIs. Conclusions Hybrid nanoparticles combined with surfactant represent a promising approach for improving PKI dissolution rate, providing increased GI absorption and bioavailability following oral administration.

Reduction of Baltic Sea Nutrient Inputs and Allocation of Abatement Costs Within the Baltic Sea Catchment - Fredrik Wulff; Christoph Humborg; Hans Estrup Andersen; Gitte Blicher-Mathiesen; Mikołaj Czajkowski; Katarina Elofsson; Anders Fonnesbech-Wulff; Berit Hasler; Bongghi Hong; Viesturs Jansons; Carl-Magnus Mörth; James C. R. Smart; et al. (Ambio, 2014)

Effects of d-amphetamine on simulated driving performance before and after sleep deprivation - Magnus Hjälmdahl; Anna Vadeby; Åsa Forsman; Carina Fors; Gunnel Ceder; Per Woxler; Robert Kronstrand (Psychopharmacology, 2012)

Phylogenetic placement and population structure of Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) off Zanzibar, Tanzania, based on mtDNA sequences - Anna Särnblad; Magnus Danbolt; Love Dalén; Omar A. Amir; Per Berggren (Marine Mammal Science, 2011)
Phylogenetic placement of bottlenose dolphins from Zanzibar, East Africa and putative population differentiation between animals found off southern and northern Zanzibar were examined using variation in mtDNA control region sequences. Samples ( n = 45) from animals bycaught in fishing gear and skin biopsies collected during boat surveys were compared to published sequences ( n = 173) of Indo‐Pacific bottlenose dolphin, Tursiops aduncus, from southeast Australian waters, Chinese/Indonesian waters, and South African waters (which recently was proposed as a new species) and to published sequences of common bottlenose dolphin, Tursiops truncatus . Bayesian and maximum parsimony analyses indicated a close relationship between Zanzibar and South African haplotypes, which are differentiated from both Chinese/Indonesian and Australian T. aduncus haplotypes. Our results suggest that the dolphins found off Zanzibar should be classified as T. aduncus alongside the South African animals. Further, analyses of genetic differentiation showed significant separation between the T. aduncus found off northern and southern Zanzibar despite the relatively short distance (approximately 80 km) between these areas. Much less differentiation was found between southern Zanzibar and South Africa, suggesting a more recent common evolutionary history for these populations than for the northern and southern Zanzibar populations.

Indications of Recovery from Hypoxia in the Inner Stockholm Archipelago - O. Magnus Karlsson; Per O. Jonsson; Dan Lindgren; J. Mikael Malmaeus; Anders Stehn (Ambio, 2010)

Variability in exchange of CO 2 across 12 northern peatland and tundra sites - MAGNUS LUND; PETER M. LAFLEUR; NIGEL T. ROULET; ANDERS LINDROTH; TORBEN R. CHRISTENSEN; MIKA AURELA; BOGDAN H. CHOJNICKI; LAWRENCE B. FLANAGAN; ELYN R. HUMPHREYS; TUOMAS LAURILA; WALTER C. OECHEL; JANUSZ OLEJNIK; et al. (Global Change Biology, 2010)
Many wetland ecosystems such as peatlands and wet tundra hold large amounts of organic carbon (C) in their soils, and are thus important in the terrestrial C cycle. We have synthesized data on the carbon dioxide (CO 2 ) exchange obtained from eddy covariance measurements from 12 wetland sites, covering 1–7 years at each site, across Europe and North America, ranging from ombrotrophic and minerotrophic peatlands to wet tundra ecosystems, spanning temperate to arctic climate zones. The average summertime net ecosystem exchange of CO 2 (NEE) was highly variable between sites. However, all sites with complete annual datasets, seven in total, acted as annual net sinks for atmospheric CO 2 . To evaluate the influence of gross primary production (GPP) and ecosystem respiration ( R eco ) on NEE, we first removed the artificial correlation emanating from the method of partitioning NEE into GPP and R eco . After this correction neither R eco ( P = 0.162) nor GPP ( P = 0.110) correlated significantly with NEE on an annual basis. Spatial variation in annual and summertime R eco was associated with growing season period, air temperature, growing degree days, normalized difference vegetation index and vapour pressure deficit. GPP showed weaker correlations with environmental variables as compared with R eco , the exception being leaf area index (LAI), which correlated with both GPP and NEE, but not with R eco . Length of growing season period was found to be the most important variable describing the spatial variation in summertime GPP and R eco ; global warming will thus cause these components to increase. Annual GPP and NEE correlated significantly with LAI and pH, thus, in order to predict wetland C exchange, differences in ecosystem structure such as leaf area and biomass as well as nutritional status must be taken into account.

AhR agonist and genotoxicant bioavailability in a PAH-contaminated soil undergoing biological treatment - Erika Andersson; Anna Rotander; Thomas von Kronhelm; Anna Berggren; Per Ivarsson; Henner Hollert; Magnus Engwall (Environmental Science and Pollution Research, 2009)

Phylogeny of babblers (Aves, Passeriformes): major lineages, family limits and classification - Magnus Gelang; Alice Cibois; Eric Pasquet; Urban Olsson; Per Alström; Per G. P Ericson (Zoologica Scripta, 2009)
Babblers, family Timaliidae, have long been subject to debate on systematic position, family limits and internal taxonomy. In this study, we use five molecular regions to estimate the relationships among a large proportion of genera traditionally placed in Timaliidae. We find good support for five main clades within this radiation, and propose a new classification, dividing the babblers into the families Sylviidae and Timaliidae. Within the latter family, four subfamilies are recognized: Zosteropinae, Timaliinae, Pellorneinae and Leiothrichinae. Several taxa, previously not studied with molecular data, are phylogenetically placed within Sylviidae or Timaliidae. This is, however, not the case for the genus Pnoepyga , for which we propose the family name Pnoepygidae fam. n.

Effects of a daily school based physical activity intervention program on muscle development in prepubertal girls - Susanna Stenevi-Lundgren; Robin M. Daly; Christian Lindén; Per Gärdsell; Magnus K. Karlsson (European Journal of Applied Physiology, 2009)

Gender differences and determinants of aerobic fitness in children aged 8–11 years - Magnus Dencker; Ola Thorsson; Magnus K. Karlsson; Christian Lindén; Stig Eiberg; Per Wollmer; Lars Bo Andersen (European Journal of Applied Physiology, 2007)

Gender differences and determinants of aerobic fitness in children aged 8–11 years - Magnus Dencker; Ola Thorsson; Magnus K. Karlsson; Christian Lindén; Stig Eiberg; Per Wollmer; Lars Bo Andersen (European Journal of Applied Physiology, 2006)

Gene Expression Profiles in Mouse Lung Tissue after Administration of Two Cationic Polymers Used for Nonviral Gene Delivery - Karin Regnström; Eva G. E. Ragnarsson; Mårten Fryknäs; Magnus Köping-Höggård; Per Artursson (Pharmaceutical Research, 2006)

Daily physical activity and its relation to aerobic fitness in children aged 8–11 years - Magnus Dencker; Ola Thorsson; Magnus K. Karlsson; Christian Lindén; Jesper Svensson; Per Wollmer; Lars Bo Andersen (European Journal of Applied Physiology, 2006)

Promoting islet cell function after transplantation - Arne Andersson; Per-Ola Carlsson; Carina Carlsson; Richard Olsson; Astrid Nordin; Magnus Johansson; Fredrik Palm; Björn Tyrberg; Örjan Källskog; Linda Tillmar; Nils Welsh; Göran Mattsson; et al. (Cell Biochemistry and Biophysics, 2004)

Promoting islet cell function after transplantation - Arne Andersson; Per-Ola Carlsson; Carina Carlsson; Richard Olsson; Astrid Nordin; Magnus Johansson; Fredrik Palm; Björn Tyrberg; Örjan Källskog; Linda Tillmar; Nils Welsh; Göran Mattsson; et al. (Cell Biochemistry and Biophysics, 2004)

Trends in urinary bladder cancer incidence in Sweden 1960-93 with special reference to histopathology, time period, birth cohort, and smoking - Magnus Thörn; Reinhold Bergström; Anna-Maria Johansson; Lars Ramström; Ingemar Persson; Per-Uno Malmström (Cancer Causes & Control, 1997)

Manganese induced brain lesions inMacaca fascicularis as revealed by positron emission tomography and magnetic resonance imaging - Håkan Eriksson; Joakim Tedroff; Karl-Åke Thuomas; Sten-Magnus Aquilonius; Per Hartvig; Karl-Johan Fasth; Peter Bjurling; Bengt Långström; Karl-Göran Hedström; Edith Heilbronn (Archives of Toxicology, 1992)

Receptor alterations in manganese intoxicated monkeys - Håkan Eriksson; Per-Göran Gillberg; Sten-Magnus Aquilonius; Karl-Göran Hedström; Edith Heilbronn (Archives of Toxicology, 1992)